Interactions between flow structure and morphodynamic of bars in a channel expansion/contraction, Loire River, France. Issue 4 (2nd April 2014) - Claude, Nicolas; Rodrigues, Stéphane; Bustillo, Vincent; Bréhéret, Jean‐Gabriel; Tassi, Pablo; Jugé, Philippe
Abstract The study of the relationship between flow structure and morphodynamic of bars in a channel expansion/contraction is essential to better understand the processes that control the evolution of rivers. Thus, multibeam echosoundings and Acoustic Doppler Profiler (ADP) measurements were performed with a high temporal resolution in an expansion/contraction zone of the Loire River (France) occupied by bars. During the monitoring period, the macroforms presented successively an alternate, a lateral and a transverse configuration. Field data were analyzed to study how the primary and secondary velocities, the flow directions, the bed shear stresses, and the bed roughnesses (associated to dunes) evolve as a function of the water discharge and bars configuration. The bars modify the flow structure imposed by the channel width variations. In fact, the bars induce a topographic forcing which enables the separation and reducing of the mixing of two currents formed in the upstream channel expansion. This forcing is enhanced by the turbulence formed by the large dunes superimposed on the bars. Therefore, the bars promote a nonuniform flow in the channel. In turn, in the channel expansion/contraction, the migrating bars' morphodynamics are affected by the downstream channel narrowing which stops their downstream migration and forced the bars in the system. Then the nonuniformity of the flow encourages the lateral migration of the macroforms until they reach a bank and become nonmigrating. Finally, the nonmigrating bars are eroded by the flow deflected during the migration of a new bar in the channel expansion/contraction.